Growth and Biochemical Changes of Vegetable Seedlings Induced by Arbuscular mycorrhizal Fungus - P. Thamizhiniyan*, R. Rajendiran, M. Lenin, G. Selvakumar (Journal of Experimental Sciences, 2010)
Department of Botany, Annamalai University, Annamalai Nagar – 608 002 <div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The efforts were made to study the effects of Arbuscular Mycorrhizal fungi (AM) on the morphological and biochemical changes of four different vegetable seedlings grown under nursery conditions. The symbiotic association between AM fungi and plant roots provides a significant contribution to plant nutrition and growth. Hence, an attempt has been made to examine the effect of AM fungi on the four vegetable crops such as Tomato (Lycopersicum esculentum L.), Brinjal (Solanum melongena L.), Chilli (Capsicum annuum L.) and Bhendhi (Abelmoschus esculentus Moench.). The maximum increase in four plant’s morphological parameters like root length, shoot length, fresh weight, dry weight, number of leaves, total leaf area and biochemical parameters like chlorophylls, proteins and nutrient content of nitrogen, phosphorus and potassium were observed in AM fungi treated seedlings when compared to non-mycorrhizal seedlings (controlled). The sugar and starch contents showed decrease in mycorrhizal seedlings than non-mycorrhizal one. Key words: Glumus fasciculatum, Vegetables, Morphological parameters, Biochemical content Department of Botany, Annamalai University, Annamalai Nagar – 608 002 M. Lenin, G. Selvakumar, P. Thamizhiniyan, R. Rajendiran. Growth and Biochemical Changes of Vegetable Seedlings Induced by Arbuscular mycorrhizal Fungus. J. Exp. Sci. 1(4):27-31 Please Cite This Article As: